Time and the shape of history - Corfield, Penelope J., 1944- (Yale University Press, 2007)
This ambitious book explores the relationship between time and history and shows how an appreciation of long-term time helps to make sense of the past. For the historian, time is not an unproblematic given but, as for the physicist or the philosopher, a means to understanding the changing patterns of life on earth. The book is devoted to a wide-ranging analysis of the way different societies have conceived and interpreted time, and it develops a theory of threefold roles of continuity, gradual change, and revolution that together form a 'braided' history. Linking the interpretative chapters are intriguing brief expositions on time travel, time cycles, time lines and time pieces, showing readers the different ways in which human history has been located in time. In its global approach the book is part of the new shift towards 'big history', in which traditional period divisions are challenged in favour of looking again at the entire past of the world from start to end. The approach is thematic. The result is a view of world history in which outcomes are shown to be explicable, once they happen, but not necessarily predictable before they do. This book will inform the work of historians of all periods and at all levels, and contributes to the current reconsideration of traditional period divisions (such as Modernity and Postmodernity), which the author finds outmoded.